(3ebGdI GdEScfOQ GdEaQhOjSi aj GdJOHjQGJ GdadcjIs - (3GdEScfOQ GdEaQhOjSis
(3ChdgG (B:s
(3bGd (B: (3Ef GdMcje PcQ ai cJGHg GdPi jOYi cJGH GdJOHjQ , Cf ZdI chf GdCTjGA GdhGbYI JMJ Gdchf hMaXgG hOhGegG ai UhQgG ai GdCLQGe G dSeGhjI s
(3BNQgG (B:s
(3JeJ ebGdI GdEScfOQ ai GdJOHjQGJ GdadcjI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(798/6) s
Keywords: (3GdadSaI hGdefWbs